Optimalisasi Pemanfaatan Daun Jati sebagai Bahan Baku Piring Ramah Lingkungan terhadap Perbedaan Kualitas Berdasarkan Musim (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The utilization of natural resources in the current era is an important concern, especially in supporting environmental sustainability. The development of awareness of environmental issues also affects the economic cycle, especially the production process of environmentally friendly goods. The running of environmentally friendly goods production in Indonesia is evidenced by the existence of various product innovations that utilize waste or natural materials, one of which is JEcoware. The existence of JEcoware is also a means of supporting business actors to carry out sustainable product innovations. One of the popular JEcoware product innovations is the utilization of teak leaves and used cardboard. The type of method used is descriptive observation with a qualitative approach. All data for this observation was obtained through literature reviews by analyzing information from various sources, as well as through the analysis of production practices carried out periodically at JEcoware. Based on the results of the discussion, it is known that the utilization of teak leaves is influenced by the season and the availability of materials to produce JEcoware products. The change of seasons also affects the quality of teak leaves due to irregular rainfall. Therefore, seasonal changes significantly impact the quality of raw materials and the JEcoware production process, ultimately influencing the production of high-quality and sustainable products.